How to improve older adults’ trust and intentions to use virtual health agents: an extended technology acceptance model - Guanhua Hou; Xinran Li; Huiwen Wang (Humanities & Social Sciences Communications)
Abstract Previous studies have examined the influence of usability, ease of use, and usefulness on enhancing older adults’ intentions to use virtual agents. However, they have overlooked the impact of doctor-patient relationships. To explore how to improve older adults’ trust and usage intentions, this study expanded Technology Acceptance Model with perceived medical narrativity, medical presence, subjective norms. Data from 230 older adults were collected through online and offline surveys. Structural equation modeling results revealed that perceived ease of use is influenced by subjective norms and perceived medical narrativity. Subjective norms influenced older adults’ medical presence, but perceived medical narrativity did not have the same effect. Medical presence is positively related to older adults’ trust, thus influencing their usage intentions. Perceived usefulness directly influences intention to use, while perceived ease of use influences intention through the mediation of trust and perceived usefulness. This study combines doctor-patient relationships factors with technology perception factors, contributing to the exploration of how social factors can be integrated into technology use.